2019
DOI: 10.3201/eid2505.181247
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Lassa Fever Cases in Nigeria, January–March 2018

Abstract: We reviewed data pertaining to the massive wave of Lassa fever cases that occurred in Nigeria in 2018. No new virus strains were detected, but in 2018, the outbreak response was intensified, additional diagnostic support was available, and surveillance sensitivity increased. These factors probably contributed to the high case count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 1 publication
4
45
0
Order By: Relevance
“…[1,2] As compared to the only 260 known human pathogenic viruses, the unknown varieties of viruses represent 99.9% of potential zoonoses, which cannot be diagnosed until symptoms are noticed. [3] Moreover, the recent unusual worldwide outbreaks of Nigerian Lassa virus in 2018, [4] Indian Nipah virus in 2018, [5] Brazilian yellow fever in 2017, [6] West African Ebola in 2017, [7] Brazilian Zika virus in 2015 [8] and worldwide coronavirus disease 2019 (COVID-19) [9] took terrible tolls, both on human life and on the global economy.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As compared to the only 260 known human pathogenic viruses, the unknown varieties of viruses represent 99.9% of potential zoonoses, which cannot be diagnosed until symptoms are noticed. [3] Moreover, the recent unusual worldwide outbreaks of Nigerian Lassa virus in 2018, [4] Indian Nipah virus in 2018, [5] Brazilian yellow fever in 2017, [6] West African Ebola in 2017, [7] Brazilian Zika virus in 2015 [8] and worldwide coronavirus disease 2019 (COVID-19) [9] took terrible tolls, both on human life and on the global economy.…”
Section: Introductionmentioning
confidence: 99%
“…LF is predominant in West Africa including Sierra Leone, Liberia and Nigeria (2). It affects 100,000 to 300,000 people every year in this region (3).There have been several LF outbreaks in various parts of Nigeria and the largest outbreak ever reported was in 2018 which shows an increasing trend in the number of cases and deaths (4) . In 2018, a total of 3016 suspected LF cases were reported from 22 states.…”
Section: Introductionmentioning
confidence: 99%
“…All the affected 22 states had at least one confirmed case spreading through 90 Local Government Areas (LGAs). Three of the 22 affected states constituted 83.0% of the confirmed cases: Edo (46%), Ondo (24%) and Ebonyi (13%) states (4). Edo State is one of the states in Nigeria with high burden of LF cases with occurrence all through the year.…”
Section: Introductionmentioning
confidence: 99%
“…LF is predominant in West Africa including Sierra Leone, Liberia and Nigeria (2). It affects 100,000 to 300,000 people every year in this region (3) There have been several LF outbreaks in various parts of Nigeria and the largest outbreak ever reported was in 2018 which shows an increasing trend in the number of cases and deaths (4). In 2018, a total of 3016 suspected LF cases were reported from 22 states.…”
Section: Introductionmentioning
confidence: 99%
“…All the affected 22 states had at least one confirmed case spreading through 90 Local Government Areas (LGAs). Three of the 22 affected states constituted 83.0% of the confirmed cases: Edo (46%), Ondo (24%) and Ebonyi (13%) states (4). This study, therefore, aimed at identifying primary spatial cluster for confirmed LF cases in Edo State, an endemic LF state, and its' associated environmental factors in the primary cluster…”
Section: Introductionmentioning
confidence: 99%